Species diversity and community composition of mosquitoes in a filariasis endemic area in Banyuasin District, South Sumatra, Indonesia - RINI PRATIWI; CHAIRIL ANWAR; SALNI SALNI; HERMANSYAH HERMANSYAH; NOVRIKASARI NOVRIKASARI; AHMAD GHIFFARI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pratiwi R, Anwar C, Salni, Hermansyah, Novrikasari, Ghiffari A, Putra R, Huda A. 2019. Species diversity and community composition of mosquitoes in a filariasis endemic area in Banyuasin District, South Sumatra, Indonesia. Biodiversitas 20: 453-462. Mosquitoes are well known as the most medically important arthropod vectors which should be monitored and evaluated because of their potential to transmit diseases. One step in monitoring and evaluation could be conducted by assessing the presence of prevalent mosquito’s vectors including their species diversity and composition. The present study has successfully recorded the diversity and community composition of mosquitoes in two villages in Banyuasin District, South Sumatra Province, Indonesia. The research was conducted for four months from December 2016 to March 2017 by collecting mosquitoes using Indoor and Outdoor Human Landing Collection method (HLC). The result shows that there were 8239 mosquitoes collected consisting of 12 genera and 38 species. Mansonia is found as the most dominant genus in Sedang Village, while in Muara Sugih Village, Culex is the most dominant. Assessment on species diversity showed that Sedang Village haes higher diversity compared to Muara Sugih Village. Further analysis indicates that environmental characteristics and presence of water plant play important role in the diversity, abundance, and dominance of mosquitoes. Waterlogged area covered with Pistia stratiotes in Sedang Village likely facilitate the breeding of Mansonia spp while extensive rice field in Muara Sugih Village may enable the high numbers of Culex spp. Anopheles spp. and Aedes spp. mosquitoes. The findings of this study suggest the rationale for the high cases of filariasis in Banyuasin District. Future research should be directed to reveal mosquitoes’ dispersal pattern and its potential as disease vector, the risk of transmitted disease, and further prevention to reduce the number of filariasis cases.